2020
DOI: 10.3390/jcm9082499
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Functional Characteristics of Patients with Unclassifiable Interstitial Lung Disease (uILD): Long-Term Follow-Up Data from European IPF Registry (eurIPFreg)

Abstract: : (1) Aim of the study: In spite of extensive research, up to 20% of interstitial lung diseases (ILD) patients cannot be safely classified. We analyzed clinical features, progression factors, and outcomes of unclassifiable ILD (uILD). (2) Methods: A total of 140 uILD subjects from the University of Giessen and Marburg Lung Center (UGMLC) were recruited between 11/2009 and 01/2019 into the European Registry for idiopathic pulmonary fibrosis (eurIPFreg) and followed until 01/2020. The diagnosis of uILD was appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
39
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 36 publications
8
39
1
Order By: Relevance
“…After final diagnostic procedures and MDTD, 16% of our patients remained non-classifiable (Fig. 1 B), which is consistent with the literature [ 8 ].…”
Section: To the Editorsupporting
confidence: 91%
“…After final diagnostic procedures and MDTD, 16% of our patients remained non-classifiable (Fig. 1 B), which is consistent with the literature [ 8 ].…”
Section: To the Editorsupporting
confidence: 91%
“…A larger proportion of our patients (34.5%) were never smokers compared to IPF (19.0-26.7%), which may partly explain the difference in the comorbidity burden [6, 14]. Krauss et al reported 38.6% never smokers in their uILD cohort, which was similar to our ndings in the present study, but lower than in cHP (50.2%) [3,12]. The spectrum of comorbidities included and differences in the approach to registration may also in uence the total number of comorbidities.…”
Section: Discussionsupporting
confidence: 83%
“…It still remains to be seen whether smoking and environmental and genetic risk factors or the underlying ILD disease is the most signi cant contributor to emphysema. Diabetes is a frequent comorbidity in IPF and other ILDs and was observed in almost 20% of our cohort [3,12,14,20]. The relationship between diabetes and brotic and/or in ammatory ILD has previously been described, but it is unclear whether diabetes is a potential risk factor for disease development or disease progression [21].…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations